2020
DOI: 10.11591/ijere.v9i4.20564
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and opinions of counselors about education of gifted students

Abstract: Counselors play effective roles not only in diagnosing but also in education of gifted students who lead the development of the societies. This study aimed to examine the attitudes and opinions of the counselors about the education of the gifted students. In the study, descriptive survey model is used. Both qualitative and quantitative data was collected within mixed method, according to the principles of pragmatist philosophy. “Attitude Scale towards Gifted Education” was applied to 250 counselors in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Kaya (2019), on the other hand, found in his research that classroom teachers' attitudes towards the education of gifted students were "undecided". Kaya and Tortop (2020) found in their study with guidance teachers that there was little positive attitude towards the education of gifted students. In studies conducted with prospective teachers, Yildirim and Oz (2018) determined that prospective teachers have positive attitudes towards gifted children and their education.…”
Section: Review Of the Literaturementioning
confidence: 92%
“…Kaya (2019), on the other hand, found in his research that classroom teachers' attitudes towards the education of gifted students were "undecided". Kaya and Tortop (2020) found in their study with guidance teachers that there was little positive attitude towards the education of gifted students. In studies conducted with prospective teachers, Yildirim and Oz (2018) determined that prospective teachers have positive attitudes towards gifted children and their education.…”
Section: Review Of the Literaturementioning
confidence: 92%
“…However, these studies found mixed results that differ from one context to another and such attitudes change with time (McCoach & Siegle, 2007). Many studies have found teachers holding positive attitudes regarding gifted students and gifted education (Alsamni, 2015;Laine, Hotulainen, & Tirri, 2019;Mojca & Urška, 2019;Kaya & Tortop, 2020). A study by Semmel et al (1991) investigated gifted education teachers' attitudes and beliefs about gifted education including pull-out classes and found that those teachers held positive attitudes.…”
Section: Educationmentioning
confidence: 99%
“…In this context, Kaya and Tortop (2020) conducted a study to investigate the attitudes and opinions of counselors about education of gifted students with a sample of 250 counselors. "Attitude Scale towards Gifted Education" was used to collect quantitative data.…”
Section: Education Of Gifted Studentsmentioning
confidence: 99%